Aspirant South African accountants’ perceptions of the usefulness of a research project as a learning tool to develop professional competency - Rudman, R.; Sexton, N. D. (South African Journal of Higher Education, 2024)
The current business climate has been described as being volatile, uncertain, complex, and ambiguous (VUCA). This new world paradigm requires new skill sets. Professional bodies are responding to changes created by this new-world paradigm that university graduates will enter with revised competency frameworks that focus on business, digital, relational, and decision-making acumen (SAICA 2021b) and include both professional (i.e., non-technical) and technical skills. Historically, accounting departments that trained chartered accountants focused on developing technical competencies in students and did not have a tradition of research. Accounting departments are investigating various teaching initiatives or tools to help develop non-technical skills in response to the changing work environment and to comply with the updated Competency Framework. Research projects, where students must formulate and investigate an unstructured question and present their findings, are used globally as a tool to develop professional competencies; however, there is limited application of research projects in the training of aspirant chartered accountants in South Africa. The 2020 cohort of postgraduate accounting students at a South African university provided a unique opportunity to investigate students’ perceptions of professional skills competency development through a group research project as very few had prior experience in conducting research. This study documents students’ perceptions of the use of the research project as a learning tool to develop specific professional competencies not traditionally taught and assessed. Although students found the research challenging, they believed that it supported the professional competency development required of future graduates that was not previously addressed appropriately.